The feasibility of relaxation-enhanced angiography without contrast and triggering for preprocedural planning of transcatheter aortic valve implantation - Wang, Rui; Liu, Xinmin; Yao, Jing; Schoepf, U. Joseph; Griffith, Joseph; Wang, Jiayang; Lian, Jianxiu; Jiang, Ke; Song, Guangyuan; Xu, Lei (Frontiers in Cardiovascular Medicine, 2023)
Background：Cardiovascular MRI has potential advantages in transcatheter aortic valve implantation (TAVI) planning. To evaluate the feasibility of a comprehensive non-contrast MRI (relaxation-enhanced angiography without contrast and triggering (REACT) combined with 3-dimensional whole heart MR protocol for preprocedural planning of TAVI versus computed tomography angiography (CTA). Methods ： Thirty patients with severe aortic stenosis were prospectively enrolled. The anatomical features of the aortic root anatomy, including perimeter and area of the virtual aortic valve annulus and coronary heights, were measured on 3D whole heart MR and cardiac CTA (CCTA) images, respectively. The diameters of the aorta (thoracic and abdominal aorta) and iliofemoral arteries were measured on REACT and aortic CTA (ACTA) images, respectively. . The paired t-test was used to compare those two modalities. Bland-Altman plots were used to assess between cardiovascular MRI and CTA measurements. Transcatheter heart valve (THV) sizing was performed based on CCTA measurements and compared to 3D whole heart MR measurements. The extent of annular calcifications on 3D whole heart MR was evaluated by a 4-point-grading scale and compared to CCTA data. Results: All 30 patients completed both CTA and cardiovascular MRI exams, with 25 administered the TAVI procedure. The mean acquisition time of the comprehensive MRI protocol was 18±3.2 minutes. There were no significant differences between ACTA and REACT in the diameters of aortic and iliofemoral arteries, including the ascending thoracic aorta (37±4.6 vs. 37.7±5.2 mm, p = 0.085), descending thoracic aorta (24.3±2.8 vs. 24.3±2.8 mm, p = 0.832), abdominal aorta (20.9±2.5 vs. 20.8±2.5 mm, p = 0.602), bilateral common iliac arteries (right: 8.36±1.44 vs. 8.42±1.27 mm, p = 0.590; left: 8.61±1.71 vs. 8.86±1.46 mm, p = 0.050), bilateral femoral arteries (right: 6.77±1.06 vs. 6.87±1.00 mm, p = 0.157; left: 6.75±1.02 vs. 6.90±0.80 mm, p = 0.142 ).Both modalities showed similar aortic valve morphology and semi-quantitative valve calcifications (all, p > 0.05). Overall agreement for implanted THV was found in 25 of 25 (100%) patients assessed with both modalities. Conclusion: REACT combined with 3D whole heart MR enables reliable measurements of aortic root anatomy, annular calcification, aorta and iliofemoral access in patients under evaluating for TAVI.